Large-scale Production and Application of Graphene Oxide Nanoparticles to Meet Agriculture Needs - Jino Affrald, R. (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2023)
The success of the agricultural sector is crucial to the whole world's prosperity. Reducing hunger and poverty and enhancing food security and nutrition have all made great strides in recent decades. Improvements in resource efficiency and food safety brought about by productivity and technical gains have not been shared fairly. Fortunately, it is possible to reduce the adverse effects of the current global food production system on the environment and climate with the aid of technological advancements. Nanotechnology can be integrated into the agricultural sciences as "nano agriculture", to provide solutions that are more accurately boost production without negatively impacting the environment. Among a range of nanoparticles, graphene oxide (GO) has found diverse application in electronics, optics, medicine, and supercapacitors. Due to its adaptability, it is also crucial in many critical biological contexts. Graphene oxide has a range of potential uses in industries as diverse as agriculture, technology, and food production. Nanoencapsulation of nutrients, smart-release systems, novel packaging, smart water treatment systems for various kinds of microorganisms and pollutants, pesticide and insecticide detection and analysis, and other kinds of detection systems are all possible applications of this versatile material. It may also be a part of fertilizer or used as a plant growth stimulant. In the GO market, yield is a major concern. With so much focus on graphene, it is essential to produce GO nanoparticles in large quantities. A possible method for industrial-scale graphene manufacturing is the oxidative exfoliation of graphite. This review outlines few cost effective strategies to mass-produce GO for use in agriculture.